Analisis Waktu Tempuh Perjalanan Penduduk Pada Yayasan Perumahan Pegawai Kantor Gubernur - Charles Kamba; Rais Rachman; Mendi Erina (Program Studi Teknik Sipil UKI Paulus-Makassar, 2023)
The rapid development of Makassar City increases the needs of the community. Makassar City has developed into a metropolitan city which has an area of ​​175.77 km2 with a population of 1,427,630 million people (BPS, 2022). As the capital of South Sulawesi Province, Makassar City has quite high transportation activities. The increase in the number of private vehicles causes several transportation problems such as congestion, longer travel times, delays and queues (Saputra, 2021). This study aims to determine the characteristics of the population and determine the variables that affect travel time and to model the travel time of residents at the Governor's Office Employee Housing Foundation. the survey in this study was carried out by distributing questionnaires to residents in housing. data analysis in this study using the method of correlation test and multiple linear regression. The results of this study can be seen that the factor that affects travel time is distance (X7). The travel time equation model for the population obtained is Y 0.578 + 0.181X6 + 0.526X7, the coefficient of determination (R2) is 39.1% and the correlation coefficient (R) is 62.5%